2000
DOI: 10.1080/000164800750000577
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Modifies the Effect ofPseudomonas aeruginosaExotoxin A on Hearing

Abstract: In the present study, the protective effect of dexamethasone was analysed following exposure of the cochlea to Pseudomonas aeruginosa Exotoxin A (PaExoA). Four groups of albino Sprague-Dawley rats were used. 20 microl saline was instilled through the tympanic membrane into the round window niche (group A, n = 4); 1 microg/20 microl dexamethasone sodium 21-phosphate (dexamethasone) solution was instilled (group B, n = 4); 1 microg/20 microl PaExoA solution was initially instilled followed 1 h later by 20 microl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The reduction of liver damage was associated with decreased serum levels of ALT, AST and icterus index. Our results were in line with the prevention of PEA-induced ototoxicity by dexamethasone [23]. Moreover, we also demonstrated that combined injection of low-dose PEA and non-toxic dose LPS synergistically caused severe liver damage, characterized by biochemical markers of liver injury.…”
Section: Discussionsupporting
confidence: 76%
“…The reduction of liver damage was associated with decreased serum levels of ALT, AST and icterus index. Our results were in line with the prevention of PEA-induced ototoxicity by dexamethasone [23]. Moreover, we also demonstrated that combined injection of low-dose PEA and non-toxic dose LPS synergistically caused severe liver damage, characterized by biochemical markers of liver injury.…”
Section: Discussionsupporting
confidence: 76%
“…aeruginosa has been used in a number of models for the study of CSOM in chinchillas [9,10], monkeys [11] and guinea pigs [12]. P. aeruginosa exotoxin A has been used in many experimental studies on the pathophysiology and treatment of middle ear infections and its complications [13,14]. The choice of animal depends on biological factors such as anatomical similarities to humans, the physiology of the Eustachian tube and susceptibility to infection, but also on non-scientific factors such as availability and cost.…”
Section: Discussionmentioning
confidence: 99%
“…19 Fortunately, nonspecific anti-inflammatory agents, such as glucocorticoids, may also modulate the damage caused by transection after exotoxin A exposure. 20 One cannot directly extrapolate observations from toxin-mediated models to conditions found in an actual infection. The dose used in the toxin model may have no bearing on the actual exposure to host tissues or the host's response to those toxins over the course of the infection.…”
Section: Discussionmentioning
confidence: 99%